Enhancing Self-Understanding in Juvenile Offenders Through Group Counseling at Marsudi Putra Social Rehabilitation Center Surabaya - Tita Amelia Ayudistya; Siti Jaro'ah (International Conference on Psychology and Education (ICPE), 2025)
Children in conflict with the law (ABH) face developmental barriers in identity formation and self-regulation due to traumatic backgrounds and inadequate support systems. This internship program at UPT PRSMP Surabaya applied social psychology principles by integrating structured group counseling and daily rehabilitation routines. Observations indicated improvements in self-confidence, emotional recognition, social communication, and personal motivation among participants. The Johari Window-based group counseling effectively promoted emotional and interpersonal self-awareness by combining guided reflections and symbolic tools like metaphorical animal character cards. As a result, participants showed greater openness, emotional clarity, and readiness for reintegration into society. This program was made possible by the Department of Psychology, Universitas Negeri Surabaya, and the support of UPT PRSMP Surabaya staff and participating juveniles.